Samoocena usposobljenosti študentk in študentov Fakultete za socialno delo - Černivec, Dino (Socialno delo, 2015)
Nowadays the future of students at the Faculty of Social Work, University of Ljubljana, is uncertain. The main problem is the Act on Balancing Public Finances, which prohibits the employment in the public sector, where social workers are usually employed. Another problem is the internship in the field of social care, the last tender for which, was in April 2013. The Ministry of Labour, Family, Social Affairs and Equal Opportunities now intends to shorten or even cancel internships so it is particularly important that students gain more work experience and competences during their study. As part of my graduation thesis, I did a survey within the 60th anniversary of education for social work in Slovenia. The aims of the research are to determine how satisfied students are with the acquired knowledge during their study at the Faculty of Social Work, how qualified they feel for work in the field of social care, what their extracurricular activities are, what they intend to do after graduating, considering they know that it is difficult to get employed, and which work experience they gained during their study practice.
Keywords: social work; socialno delo; studies; študij; education; izobraževanje; kompetence; competences; Bologna process; bolonjski proces